Polyethyleneimine coating of magnetic particles increased the stability of an immobilized diglycosidase - Minig, Paola Marisol (2015)
The diglycosidase, α-rhamnosyl-β-glucosidase, from Acremonium sp. DSM24697 was immobilized by adsorption and cross-linking onto polyaniline-iron (PI) particles. The immobilization yield and the immobilization efficiency were relatively high, 31.2% and 8.9%, respectively. However, the heterogeneous preparation showed lower stability in comparison with the soluble form of the enzyme in operational conditions at 60 °C. One parameter involved in the reduced stability of the heterogeneous preparation was the protein metal-catalyzed oxidation achieved by iron traces supplied from the support. To overcome the harmful effect, iron particles were coated with polyethyleneimine (PEI; 0.84 mg/g) previously for the immobilization of the catalyst. The increased stability of the catalyst was correlated with the amount of iron released from the support. Under operational conditions, the uncoated particles lost between 76% and 52% activity after two cycles of reuse, whereas the PEI-coated preparation reduced 45-28% activity after five cycles of reuse in the range of pH 5.0-10, respectively. Hence, polymer coating of magnetic materials used as enzyme supports might be an interesting approach to improve the performance of biotransformation processes.